Peace-making and the settlement with Japan - Dunn, Frederick Sherwood, 1893-1962 (Princeton legacy library., 1963)
Analyzes the change in national attitudes after the outbreak of World War II, the San Francisco conference and treaty, and the effect of settlement on the security of the West. Originally published in 1963. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.